Alzheimer and Purinergic Signaling: Just a Matter of Inflammation? - Stefania Merighi; Tino Emanuele Poloni; Anna Terrazzan; Eva Moretti; Stefania Gessi; Davide Ferrari (Cells, 2021)
Alzheimer’s disease (AD) is a widespread neurodegenerative pathology responsible for about 70% of all cases of dementia. Adenosine is an endogenous nucleoside that affects neurodegeneration by activating four membrane G protein-coupled receptor subtypes, namely P1 receptors. One of them, the A2A subtype, is particularly expressed in the brain at the striatal and hippocampal levels and appears as the most promising target to counteract neurological damage and adenosine-dependent neuroinflammation. Extracellular nucleotides (ATP, ADP, UTP, UDP, etc.) are also released from the cell or are synthesized extracellularly. They activate P2X and P2Y membrane receptors, eliciting a variety of physiological but also pathological responses. Among the latter, the chronic inflammation underlying AD is mainly caused by the P2X7 receptor subtype. In this review we offer an overview of the scientific evidence linking P1 and P2 mediated purinergic signaling to AD development. We will also discuss potential strategies to exploit this knowledge for drug development.